Pendidikan Anti Korupsi Sebagai Upaya Pencegahan Tindak Pidana Korupsi - Sutanto, Alex Tribuana (Terekam Jejak Publisher, 2024)
The high number of corruption cases in Indonesia requires schools to play an active role in instilling the values of integrity and motivating students to participate in efforts to prevent and eradicate criminal acts of corruption. This research was conducted to analyze efforts of preventing and eradicating about criminal acts of corruption through anti-corruption education in schools. The research was carried out in a normative juridical manner using qualitative descriptive analytical methods. The results of the research are that Anti-Corruption Education for school students provides motivation in efforts to prevent criminal acts of corruption through guidance on values education, namely good values. The Anti-Corruption Education learning model also needs to be an interesting subject and not monotonous. The material presented must strengthen cognitive aspects, and choosing creative learning methods is the key to success by optimizing students' intellectual, critical nature and ethical integrity, in which competent educators can fulfill roles as communicators, facilitators, and motivators.